Targeting Autophagy for the Treatment of Alzheimer’s Disease: Challenges and Opportunities - Liu, Jie; Li, Lian (Frontiers in Molecular Neuroscience, 2019)
Alzheimer’s disease (AD) is the most common type of dementia which characterized by a progressive loss of memory and cognitive function due to degeneration of synapses and axons. Currently, there is no cure for AD. Deposition of extracellular amyloid-β (Aβ) plaques and intracellular tau neurofibrillary tangles (NFTs) are two hallmark pathologic changes in the brains of Alzheimer’s patients. Autophagy is the major mechanism in cells responsible for removing protein aggregates. Accumulation of immature autophagic vacuoles (AVs) in dystrophic neurites of Alzheimer patients’ brains suggests that autophagy process is disrupted. Till now, it is far from clear what role autophagy plays in AD, a causative role, a protective role, or just a consequence of the disease process itself. To design more effective therapeutic strategies towards this devastating disorder, it is essential to understand the exact role of autophagy played during different stages of AD.